The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1007/s11010-015-2535-7
|View full text |Cite
|
Sign up to set email alerts
|

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma

Abstract: NF45, also referred to as nuclear factor of activated T cells, has been reported to promote the progression of multiple cancer types. However, the expression and physiological significance of NF45 in pancreatic ductal adenocarcinoma (PDAC) remain largely elusive. In this study, we investigated the clinical relevance and potential role of NF45 expression in PDAC development. Western blot analysis revealed that NF45 was remarkably upregulated in PDAC tissues, compared with the adjacent non-tumorous ones. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
(37 reference statements)
2
18
0
Order By: Relevance
“…It has been reported that ILF2 is abundantly expressed in pancreatic carcinoma (8) and it functions as an oncogene. Thus, we aimed to elucidate the mechanisms underlying the increased ILF2 expression in pancreatic carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that ILF2 is abundantly expressed in pancreatic carcinoma (8) and it functions as an oncogene. Thus, we aimed to elucidate the mechanisms underlying the increased ILF2 expression in pancreatic carcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ILF2 may be a potential therapeutic target (8). Yet, the regulatory mechanisms of ILF2 remain largely elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…disruption of NF90 and NF45 impaired ESC proliferation and promoted differentiation to an epiblast-like state (27). NF90 and NF45 regulate cell cycle progression (18,19,28), cell growth and proliferation (28)(29)(30)(31)(32)(33), and are amplified, overexpressed and mutated in diverse cancers (34,35).…”
Section: Introductionmentioning
confidence: 99%